Zymophagy: Selective Autophagy of Secretory Granules - Maria I. Vaccaro (International Journal of Cell Biology)
Timing is everything. That's especially true when it comes to the activation of enzymes created by the pancreas to break down food. Pancreatic enzymes are packed in secretory granules as precursor molecules called zymogens. In physiological conditions, those zymogens are activated only when they reach the gut, where they get to work releasing and distributing nutrients that we need to survive. If this process fails and the enzymes are prematurely activated within the pancreatic cell, before they are released from the gland, they break down the pancreas itself causing acute pancreatitis. This is a painful disease that ranges from a mild and autolimited process to a severe and lethal condition. Recently, we demonstrated that the pancreatic acinar cell is able to switch on a refined mechanism that could explain the autolimited form of the disease. This is a novel selective form of autophagy named zymophagy, a cellular process to specifically detect and degrade secretory granules containing activated enzymes before they can digest the organ. In this work, we revise the molecules and mechanisms that mediate zymophagy, a selective autophagy of secretory granules.